Comprehensive liquid biopsy analysis for monitoring NSCLC patients under second-line osimertinib treatment - Ntzifa, Aliki; Marras, Theodoros; Kallergi, Galatea; Kotsakis, Athanasios; Georgoulias, Vasilis; Lianidou, Evi (Frontiers in Oncology, 2024)
BackgroundThe heterogeneous and complex genetic landscape of NSCLC impacts the clinical outcomes of patients who will eventually develop resistance to osimertinib. Liquid biopsy (LB) analysis as a minimally invasive approach is a key step to efficiently identify resistance mechanisms and adjust to proper subsequent treatments. Materials and methodsIn the present study, we combined plasma-cfDNA and CTC analysis from 30 NSCLC patients in samples collected before treatment and at the progression of disease (PD). We detected molecular alterations at the DNA mutation (EGFR, PIK3CA, KRAS G12C, BRAF V600E), DNA methylation (RASSF1A, BRMS1, FOXA1, SLFN1, SHISA3, RARβ,, WIF-1, RASSF10 and APC), gene expression (CK-19, CK-18, CK-8, AXL, TWIST-1, PD-L1, PIM-1, Vimentin, ALDH-1, and B2M) and chromosomal level (HER2 and MET amplification) as possible resistance mechanisms and druggable targets. We also studied the expression of PD-L1 in single CTCs using immunofluorescence.ResultsIn some cases, T790M resistance EGFR mutation was detected at baseline in CTCs but not in the corresponding plasma cfDNA. PIK3CA mutations were detected only in plasma-cfDNA but not in corresponding CTCs. KRAS G12C and BRAF V600E mutations were not detected in the samples analyzed. MET amplification was detected in the CTCs of two patients before treatment whereas HER2 amplification was detected in the CTCs of three patients at baseline and in one patient at PD. DNA methylation analysis revealed low concordance between CTCs and cfDNA, indicating the complementary information obtained through parallel LB analysis. Results from gene expression analysis indicated high rates of vimentin-positive CTCs detected at all time points during osimertinib. Moreover, there was an increased number of NSCLC patients at PD harboring CTCs positive in PD-L1. AXL and PIM-1 expression detected in CTCs during treatment suggesting new possible therapeutic strategies. DiscussionOur results reveal that comprehensive liquid biopsy analysis can efficiently represent the heterogeneous molecular landscape and provide prominent information on subsequent treatments for NSCLC patients at PD since druggable molecular alterations were detected in CTCs.